Path Analysis on Factors Affecting the Use of Hemodialysis in Patients Chronic Renal Disease at Dr. Soehadi Prijonegoro Hospital Sragen, Central Java - Anisa Andriani; Didik Gunawan Tamtomo; Bhisma Murti (Journal of Health Policy and Management, 2021)
Background: Patient adherence can be influenced by several factors that can affect compliance with hemodialysis treatment. Adherence is highly treated while undergoing hemodialysis in order to achieve success in hemodialysis (HD) treatment. Adherence is one of the behaviors of a person in achieving successful HD treatment. The success of a treatment can be influenced by several factors, one of which is the use of HD. This study aimed to determine the effect of compliance with hemodialysis.Subjects and Method: The was an observational analytic study with a cross-sectional design. The study was conducted in January 2020. The sample used was 120 chronic kidney failure patients undergoing hemodialysis at Dr. Soehadi Prijonegoro Sragen Hospital. The dependent variable was compliance with hemodialysis. The independent variables are: knowledge, length of care, family income. Data were collected by means of a questionnaire. Data analysis was performed using path analysis with Stata 13.Results: The use of HD in patients with chronic renal failure had a positive association with high HD knowledge (b= 1.22; 95% CI= 2.21 to -3.98; p= 0.027), length of stay (b= 2.09; 95% CI= 4.29 to 3.05; p<0.001), and has no positive relationship with family income (b = 0.40; 95% CI = 0.80 to 1.41; p = 0.426). The use of HD in patients with chronic renal failure is influenced indirectly by family income and length of treatment.Conclusion: The use of HD in chronic renal failure patients has a direct relationship with knowledge of HD and length of treatment, and has no direct relationship with family income. The use of HD in patients with chronic renal failure is influenced indirectly by family income and length of treatment.Keywords: hemodialysis, chronic renal failureCorrespondence: Anisa Andriani. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: andrianianisa390@gmail,com. Mobile: +6282220826660.Journal of Health Policy and Management (2021), 06(01): 13-20https://doi.org/10.26911/thejhpm.2021.06.01.02